DYNAMIC GOVERNANCE DALAM PENGEMBANGAN PARIWISATA DI KAWASAN RESORT PENGELOLAAN HUTAN MANGUNAN KABUPATEN BANTUL - Syarif Nurizwan; Utami Dewi (NATAPRAJA, 2018)
Mangunan Forest Management Resort as a tourism area needs dynamic capability of stakeholders to adjust various future needs, sustainability and improvement of problems. This study aimed to analyze the dynamic capabilities aspects of Dynamic Governance in the development of tourism in RPH Mangunan and its inhibited factors. The research design used descriptive with qualitative approach. The results of this study showed that RPH Mangunan had paid attention to the three aspects dynamic capability of Dynamic Governance, that was Think Ahead, Think Again and Think Across. The inhibited factors of Dynamic Governance were: 1) Low quality of human resources 2) Lack of coordination between stakeholders, especially related to the development of tourism infrastructure 3) limited budget.